2005
DOI: 10.1189/jlb.1204711
|View full text |Cite
|
Sign up to set email alerts
|

Differential capability for phagocytosis of apoptotic and necrotic leukemia cells by human peripheral blood dendritic cell subsets

Abstract: CD11c+ dendritic cells (DC) and plasmacytoid DC (PDC) are the two major DC subsets in human peripheral blood. For the purpose of immunotherapy with DC, it is important to investigate the phagocytosis of killed tumor cells by different DC subsets. Using immature monocyte-derived DC (iMoDC) as reference, we have compared the ability of CD11c+ DC and PDC to phagocytose apoptotic and necrotic K562 leukemia cells. Freshly isolated CD11c+ DC phagocytosed apoptotic and necrotic K562 cells, whereas PDC did not show an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 51 publications
1
49
1
Order By: Relevance
“…First,the composition of the studied particulates(apoptotic cells, beads, bacteria, or PLGA microparticles) is diverse and uptake might require different receptors and uptake mechanisms, some of which may not be exploited by pDCs. Furthermore, some studies compared the phagocytic capacity of pDCs to that of moDCs and found that pDCs showed very little to no uptake compared with moDCs (3,14,18). We also found that moDCs were superior to pDCs in phagocytosing particulate Ag, notwithstanding that almost all pDCs engulfed particles.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…First,the composition of the studied particulates(apoptotic cells, beads, bacteria, or PLGA microparticles) is diverse and uptake might require different receptors and uptake mechanisms, some of which may not be exploited by pDCs. Furthermore, some studies compared the phagocytic capacity of pDCs to that of moDCs and found that pDCs showed very little to no uptake compared with moDCs (3,14,18). We also found that moDCs were superior to pDCs in phagocytosing particulate Ag, notwithstanding that almost all pDCs engulfed particles.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, we investigated whether pDCs can play a role in immune responses against exogenous particulates. Up to now, it was highly controversial whether pDCs are able to respond to stimuli entrapped in particle-like structures (3,8,9,14,(16)(17)(18)(19). We demonstrate that pDCs are clearly capable of phagocytosing Ag entrapped within PLGA microparticles and subsequent processing of the encapsulated Ag.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ability of human DC to capture necrotic/ apoptotic cells has been demonstrated with either MDDC [21,31,45,46] or blood mDC [47]. Mouse LC were shown to phagocytose many types of particles [48].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, another type of DC, the plasmacytoid DC (PDC), responds specifically to RNA/DNAcontaining immune complexes by producing the type I interferon interferon-␣ (IFN␣), which seems crucially involved in the pathogenesis of SLE (27,28). However, ingestion of apoptotic cells by PDCs is unlikely to occur (29).…”
mentioning
confidence: 99%